Kefektifan Penggunaan Media Pembelajaran Puzzle Terhadap Prestasi Belajar PAI Siswa Kelas IV Sekolah Dasar - Fathin, Arif Faisal; Malahati, Fildza; Kadir, Sitti Fatimah; Kumalasari, Ika Dyah (Institut Agama Islam Negeri Kendari, 2023)
This study aims to determine the effectiveness of using puzzle learning media on PAI learning achievement in matters of faith in angels in grade IV of elementary school. The data in this study were obtained by using pretest and posttest. The collected data were analyzed using the normality test, homogeneity test, hypothesis testing, and t-test techniques. The results of this study indicate that puzzle learning media is more effective than picture media in improving PAI learning achievement. The results of the research showed that there was a significant increase in PAI learning achievement for students who carried out learning activities using puzzle media, whereas for students who carried out learning activities using picture media there was an increase but the results were not very significant.